kajian heuristik dan hermeneutik terhadap kumpulan puisi deru campur debu karya chairil anwar - muchti, andina (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2017)
All of the literature studies are related to the activity of interpretation. One of literature types that can be interpreted is poetry. To interpret a poem can involve the role of heuristics and hermeneutics concept. This study used several poems contained in the book of poetry Deru Campur Debu by Chairil Anwar. The problems of this study, namely 1) How do heuristic and hermeneutic reading on the poem of Chairil Anwar, and 2) What are the meaning of language and literature contained in the poem of Chairil Anwar. Heuristic and hermeneutic readings are the method to analyze literary works by using semiotic approach. Semiotics is a term that refers to the same thing that is the sign science. The relationship between signifier and signified included, icons, indices, and symbols. The results of this study are as follows: 1. In the sixth poems of Chairil Anwar always brings the themes of freedom, rebellion and adventure that are the expression of Chairils characteristic himself. 2. The unpleasant experience of dating with Hayati made him upset and dreaming of a lover who was very different from Hayati. therefore, Chairil express it with harsh words to describe the regret